The Relationship between Anthropometric Measurements and Vitamin D Levels and Insulin Resistance in Obese Children and Adolescents - Emrah Çığrı; Funda Çatan İnan (MDPI AG, 2022)
Objective: Our investigation aimed to determine the effect of vitamin D levels on the development of insulin resistance in obese adolescents and children and the influences of anthropometric measurements on predicting the development of insulin resistance. Materials and Methods: In this study, demographic data, laboratory findings, and anthropometric measurements of 150 adolescents and children that had obesity diagnoses between May 2021 and September 2022 were evaluated retrospectively. Those with and without insulin resistance were studied with regard to vitamin D levels, biochemical parameters, and anthropometric measurements. Three groups of patients were created: those with low levels of vitamin D (<20 ng/mL), those with insufficient levels (20-30 ng/mL), and those having normal levels (≥30 ng/mL). Groups were compared in terms of homeostatic model score (HOMA-IR) and anthropometric measurements. Correlation analysis was carried out to ascertain the correlation of anthropometric measurements with HOMA-IR. To ascertain the cutoff, specificity, and sensitivity values of anthropometric parameters in predicting insulin resistance in patients, receiver operating characteristic (ROC) analysis was carried out. Results: Vitamin D levels of obese adolescents and children with insulin resistance were substantially lower than those without insulin resistance (p < 0.001). As the vitamin D level increased, all anthropometric measurements except for the body fat percentage decreased significantly with the HOMA-IR score (p < 0.05). HOMA-IR demonstrated a strong positive relation with waist circumference (rs = 0.726, p < 0.001). Waist circumference had high specificity and sensitivity in predicting insulin resistance (87.3% and 87.4%, respectively). Conclusions: A significant relationship was observed between insulin resistance development and low levels of vitamin D in obese children and adolescents. As vitamin D levels increase, anthropometric measurements are more stable and do not increase. Waist circumference is the most effective anthropometric measurement for predicting the development of insulin resistance in obese adolescents and children.